On the Impossible: Disability Studies, Queer Theory, and the Surviving Crip - Bailey, Courtney W. (Disability Studies Quarterly, 2019)
Drawing on my personal experiences with chronic pain, depression, and abuse, this essay critiques both the anti-cure strand in disability studies and the anti-relational strand in queer theory. I argue that anti-cure politics evokes a fantasy of the naturally impaired body-mind, a kind of disabled normate, which ultimately abjects those who cannot transcend their disabilities. Queer theory's willingness to embrace negativity provides a useful counter-point to this impluse, yet its turn to negativity produces its own problems, most clearly articulated in its anti-relational strand. This strand relies on psychoanalysis as a closed symbol system divorced from history, politics, and materiality and touts the self-annihilating queer as the site of revolution. Both the disabled normate and self-annihilating queer risk replicating the mind/body dualism that undergirds Western culture's View from Nowhere and liberal humanism's sovereign subjectivity. Inspired by concepts like the queer art of failure, dignity in shame, the feminist killjoy, and cruising utopia, I ultimately suggest the figure of the "surviving crip" as a generative alternative to dominant culture's super-crip, anti-cure's disabled normate, and the anti-relational, self-annihilating queer. Far from a perfect solution, the figure of the surviving crip is a starting place, a heuristic for critical-political ethics, and an invitation to other reworkings and other reckonings.